377 Global Recruitment for The RESECT Study (Transurethral Resection and Single-Instillation Intravesical Chemotherapy Evaluation in Bladder Cancer Treatment): An International Observational Cohort Study Aiming to Improve the Quality of Surgery for Non-Muscle Invasive Bladder Cancer. (4th May 2021) - Light, A; Gallagher, K; Bhatt, N; Clement, K; Kulkarni, M a; Khadhouri, S; Zimmermann, E; Gao, C; Lam, C; Anbarasan, T; Chan, V; Rossi, S; et al.
Abstract: Introduction: Non-muscle invasive bladder cancer (NMIBC) can be curatively treated with 'good quality' transurethral resection of the bladder tumour (TURBT). However, despite evidence-based international guidelines, there is anecdotal evidence that practice varies widely, and this may affect oncological outcomes. Launching in 2020, RESECT aims to measure and report variation in TURBT quality globally, and determine if outcome reporting improves outcomes. Method: RESECT was advertised internationally through social media, mailing lists, websites, and in person. Collaborators at each registered site will collect data about current practice and the experience of local TURBT surgeons. The primary outcome is the rate of achievement of key TURBT quality indicators. Results: As of August 27, 508 collaborators have registered to participate. Collaborators represent 321 centres from 54 countries, with the highest number from the United Kingdom (54.5%), Spain (5.9%), and Argentina (3.7%). 51.2% are trainees, 29.9% consultants, and 17.5% medical students. Based on current registrations, patient recruitment will far exceed initial projections and considerably improve statistical power. Conclusions: RESECT has attracted a large number of collaborators globally and from all training levels. Therefore, the RESECT study has the potential to improve the quality of TURBT surgery across the world.